The Innovative Model of Energy Efficient Village under the Conditions of Sustainable Development of Ecological Territories - YASNOLOB, Ilona; CHAYKA, Tetyana; GORB, Oleg; Demianenko, Nataliia; PROTAS, Nadiia; HALINSKA, Tetіana (Journal of Environmental Management and Tourism, 2018)
The topicality of raising the level of rural territories’ energy independence is substantiated in the article. Using the Ukrainian and foreign experience in creating and implementing the projects “energy efficient village”, the stages of its introduction have been determined. Taking into account the results of these projects in Ukraine, the conditions as to providing their efficiency have been defined. The peculiarities of creating the energy independent and effective village have been considered; its conceptual model has been created. Some aspects of using biomass and its effectiveness as an alternative source of energy have been presented. The factors of ecological, social, and economic efficacy of developing and implementing the projects of “energy efficient village” on the rural territories of Ukraine have been determined. The actuality of developing and introducing the projects in the creation of energy independent rural territories is put into practice on the territory of Ukraine.